Influence of the type of educational center on the attitudes of young people towards doping - Ruiz-Rico Ruiz, G. J.; Zurita Ortega, F.; Castro Sánchez, M.; Chacón Cuberos, R.; Cachón Zagalaz, J.; Valdivia Moral, P. A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The phenomenon of the doping is not only instated in the world of the professional sport, also it is damaging increasingly inside the sport amateur and recreational. As the age of the persons who use it is diminishing along the time, the present investigation considers as aim analyzing and establishing relations between the young students' attitudes about the doping, depending on the type of school (public or concert / private) where young people study. In this investigation, 839 students between 15 and 18 years participated in(M=16.22 years, DT =.77), it allowed the record and evaluation of the variables type of school center and attitudes towards the doping, for his data collect we use the scale of attitudes towards the doping (PEAS) of Petróczi (2002). The results revealed that the majority of the participants have attitudes that reject doping (64,2%; n=539); the pupils who were schooled in public centers have more vulnerable attitudes towards the doping (p=.014).